Structure of the brachial plexus root and adjacent regions displayed by ultrasound imaging - Li, Zhengyi; Xia, Xun; Rong, Xiaoming; Tang, Yamei; Xu, Dachuan (Neural regeneration research, 2012)
Brachial plexuses of 110 healthy volunteers were examined using high resolution color Doppler ultrasound. Ultrasonic characteristics and anatomic variation in the intervertebral foramen, interscalene, supraclavicular and infraclavicular, as well as the axillary brachial plexus were investigated. Results confirmed that the normal brachial plexus on cross section exhibited round or elliptic hypoechoic texture. Longitudinal section imaging showed many parallel linear hypo-moderate echoes, with hypo-echo. The transverse processes of the seventh cervical vertebra, the scalene space, the subclavian artery and the deep cervical artery are important markers in an examination. The display rates for the interscalene, and supraclavicular and axillary brachial plexuses were 100% each, while that for the infraclavicular brachial plexus was 97%. The region where the normal brachial plexus root traversed the intervertebral foramen exhibited a regular hypo-echo. The display rate for the C5-7 nerve roots was 100%, while those for C8 and T1 were 83% and 68%, respectively. A total of 20 of the 110 subjects underwent cervical CT scan. High-frequency ultrasound can clearly display the outline of the transverse processes of the vertebrae, which were consistent with CT results. These results indicate that high-frequency ultrasound provides a new method for observing the morphology of the brachial plexus. The C~ vertebra is a marker for identifying the position of brachial plexus nerve roots.